2021
DOI: 10.1111/his.14555
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between core needle biopsy and surgical excision specimens for Ki‐67 in breast cancer – a systematic review of the literature

Abstract: Concordance between core needle biopsy and surgical excision specimens for Ki-67 in breast cancera systematic review of the literature Aims: The biomarkers oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) are routinely measured in patients with breast cancer with international consensus on how they should be interpreted. There is evidence to support use of other biomarkers to give more detailed predictive and prognostic information. Ki-67 is one example, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(227 reference statements)
0
8
0
Order By: Relevance
“…Additional support for the conclusion that the difference in Ki67 between CB and WS is provided by the observation of clinically relevant differences between specimens in cases from different institutions used in this study, independently scored multiple times by 17 pathologists. Although many studies focused on assessing the level of agreement between CB and resection samples in Ki67 scoring; consensus was not possible due to lack of standardization 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for the conclusion that the difference in Ki67 between CB and WS is provided by the observation of clinically relevant differences between specimens in cases from different institutions used in this study, independently scored multiple times by 17 pathologists. Although many studies focused on assessing the level of agreement between CB and resection samples in Ki67 scoring; consensus was not possible due to lack of standardization 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al also confirmed the heterogeneity in HER2-Low breast cancers by using another two similar microarray-based genomic profile analyses, MammaPrint and BluePrint [ 17 ]. In addition, the technical aspects of HER2 testing methods are likely a major reason for the HER2 discrepancy [ 8 , 31 ]. According to the current guidelines, the IHC/FISH test is a reliable tool to differentiate HER2-Positive tumors from HER2-Negative tumors [ 32 ], while the lower boundary of HER2-Low diagnosis seems to be more confusing.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the method of sampling also has a great influence on the HER2 expression test. CNB is a minimally invasive preoperative examination for early diagnosis and (neo)adjuvant strategy decision making, but the relatively small amount of biopsy tissue available for examination is an inevitable restriction for an accurate result [ 31 ]. Although previous research has demonstrated the high accuracy of ER, PR, Ki67 and HER2 as dichotomous variables ( Supplementary Table S3 ), our current study showed a relatively lower concordance rate in HER2-Low status diagnosis by CNB; thus, retesting HER2 status with a larger sample size after radical surgery could provide a more precise diagnosis, especially for HER2-Low status detection.…”
Section: Discussionmentioning
confidence: 99%
“…For patients initially treated by surgery, the task force recommends testing a core biopsy when possible, but a whole well-fixed section from untreated breast tissue is an acceptable alternative. There is a high but not perfect concordance between paired core biopsies and whole sections from resection specimens, with the scores being systematically higher in core biopsies, possibly due to more controlled preanalytical variables [ 22 , 23 , 24 ]. Tissue fixed in alcohol-based fixatives, often used in cytology preparation, as well as decalcified tissue, should be avoided.…”
Section: Questions To Addressmentioning
confidence: 99%